EFEKTIFITAS KETERAMPILAN PENGOLAHAN KELAPA MENJADI KOPRA MELALUI METODE LATIHAN BAGI ANAK TUNAGRAHITA RINGAN DI SDLBN 20 PONDOK II PARIAMAN - Yeni Basra, Ardisal, Tarmansyah (Jurnal Penelitian Pendidikan Khusus, 2013)
The research background of the problems that researchers found in a child's mild tunagarahita SDLB fourth grade C at N 20 huts II Pariaman are not skilled in the coconut into copra processing skills especially in drying by sunlight through training methods, and these skills have not been in taught in school. This type of research is experimental research in the form of single subject reseach (SSR) using ABA design and data analysis techniques using visual analysis chart. Subjects were mild mental retardation children. Assessment in this study is to measure the percentage of children's ability to scale the attitude or actions of coconut into copra drying in the sun. Based on the results of research, looks capabilities of coconut into copra processing skills can be improved with training methods At baseline conditions (A1) The first meeting until five meetings up and down the child's ability, by changing the data range of 0%, and 16.7%, so that researchers halted the observation in this condition at the fifth meeting, in which the data were obtained stable of meeting three to five percentage obtained child is 0%. While in the intervention condition (B) observations of eight meetings, the first meeting of this meeting 33.3% in the data obtained up and down, but still above 33.3%, the second meeting rose to 66.7%, in the third meeting 50% , meetings of four to 66.7%, the percentage obtained five children is 83.3%, the sixth meeting of up to 100% up to eight meetings, observations stopped at the eighth meeting of the data has shown a steady increase, Son was able to finish kerterampilan drying by sun drying method with 6 steps correctly. At baseline session (A2) conducted four meetings, At the first meeting of the percentage of children who obtained 66.7%, 83.3% at the second meeting to meeting to four. Thus the hypothesis (Ha) proposed acceptable, the method of training can be used for effective processing of coconuts into copra skills for children mild mental retardation. This means that both training methods used by teachers in the learning skills because of its method of repetitive exercise.